2020
DOI: 10.1111/tbed.13477
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of variant infectious bronchitis virus in China, 2019: Implications for control programmes

Abstract: Infectious bronchitis virus (IBV), an ongoing emergence enveloped virus with a singlestranded positive-sense RNA genome, belongs to the Gammacoronavirus genus in the Coronaviridae family. IBV-associated tracheitis, nephritis, salpingitis, proventriculitis and egg drop have caused devastating economic losses to poultry industry worldwide. Since the end of 2018, a remarkably increasing number of commercial broilers and layers, vaccinated or not, were infected with IBV in China. Here, we described two IB outbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 25 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…SARS-CoV-2 has the ability to cross the species barrier, which makes it possible to infect humans, whereas COVID-19-positive humans facilitate the reverse zoonotic transmission of the virus from human to animals (Fig. 1) (Parry, 2020;Zhang et al, 2020b). Among the reported animals, an infected dog did not show any clinical signs, unlike cats.…”
Section: Coronavirus Disease 2019 In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 has the ability to cross the species barrier, which makes it possible to infect humans, whereas COVID-19-positive humans facilitate the reverse zoonotic transmission of the virus from human to animals (Fig. 1) (Parry, 2020;Zhang et al, 2020b). Among the reported animals, an infected dog did not show any clinical signs, unlike cats.…”
Section: Coronavirus Disease 2019 In Animalsmentioning
confidence: 99%
“…Other CoVs from the deltacoronavirus genus include Bulbul coronavirus HKU11, Wigeon coronavirus HKU20, White-eye coronavirus HKU16, Common moorhen coronavirus HKU21, Munia coronavirus HKU13, and Night-heron coronavirus HKU19 that can severely infect birds with more complications (Paim et al, 2019). Even though there were different attempts for effective vaccine development against the CoVs, the rapid mutations and antigenic variations created a hindrance to successfully trigger the local immune response and cure infections (Saif, 2020;Zhang et al, 2020b). Viruses from alphacoronavirus, betacoronavirus, and deltacoronavirus affect the porcine population.…”
Section: Donkey and Dromedary Camelmentioning
confidence: 99%
“…The new IBV strain sequences isolated in 2018 from Lebanon were made available in the GenBank database, and our analysis based on these sequences confirmed their clustering with the GI-23 strain. In addition, recently released Syrian IBV strain HVR3 sequences have been determined to belong to the GI-23 [22,126,127] genotype. However, no associated publications have been found in either country (Table 3).…”
Section: Lebanon and Syriamentioning
confidence: 99%
“…BCoV also has a wide host range, including dogs, poultry, and giraffes. Genomic analysis revealed that BCoV shows only 49.2-49.3% gene similarity to SARS-CoV-2 (Zhang et al, 2020a).…”
Section: Origin and Evolution Of Sars-cov-2mentioning
confidence: 99%